O gênero Aulonemia Goudot ( Poaceae: Bambusoideae: Bambuseae) no Brasil - Pedro Lage Viana (2010)
Aulonemia Goudot is woody bamboo genus (Bambuseae tribe) that belongs to the Neotropical subtribe Arthrostylidiinae. The 38 known species are distributed from Mexico to southern Brazil and are usually related to high altitude environments. This thesis is a study of the genus in Brazil and includes a taxonomic treatment, an investigation on leaf anatomy and a proposition of a new genus segregated form Aulonemia. This thesis is composed of three chapters. Chapter 1 is a taxonomic treatment of the genus Aulonemia in Brazil and includes keys for identification of the species, detailed morphological descriptions, geographic distribution, ecological and conservation data. For this study, Brazilian and non-Brazilian herbaria were sampled and intensive field work was conducted. A total of 14 species were accepted to occur in Brazil, five of these new to science. Chapter 2 is a study on leaf anatomy of the Brazilian species of Aulonemia, with emphasis on the importance of anatomical characters for taxonomy of the genus. Different regions of the leaf blade were sampled on optical microscopy (cross section and epidermis) and scanning electron microscopy (epidermis). Some characters were considered useful for taxonomy of the genus, like the distribution pattern of intercostal sclerechyma, type of vascular system 3 in the midrib, type and distribution of papillae on the epidermis, and pattern of distribution of stomata. And in chapter 3 is presented a new genus of the subtribe Arthrostylidiinae segragated from Aulonemia, which is corroborated by morphological and phylogenetic data. Detailed morphological and anatomical descriptions are provided, as well as plates with important characters and a comparison with the related genera of Arthostylidiinae subtribe. This study is an advance to the knowledge of the Brazilian bamboos and opens the way for future investigations on other approaches.